2019
DOI: 10.7717/peerj.7589
|View full text |Cite
|
Sign up to set email alerts
|

Sargassumblooms in the Caribbean alter the trophic structure of the sea urchinDiadema antillarum

Abstract: The arrival of large masses of drifting Sargassum since 2011 has caused changes in the natural dynamics of Caribbean coastal ecosystems. In the summer of 2015, unprecedented and massive mats of S. fluitans and S. natans have been observed throughout the Mexican Caribbean including exceptional accumulations ashore. This study uses stable isotopes to assess the impact of Sargassum blooms on the trophic dynamics of the Diadema antillarum sea urchin, a keystone herbivore on many Caribbean reefs. Bayesian models we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(29 citation statements)
references
References 105 publications
(153 reference statements)
0
29
0
Order By: Relevance
“…The drifting mats of sargasso may also serve as a vector for many non-native species [82]. Sargasso also affects the food webs; Cabanillas et al [84] found that sea urchins had changed their diet from reef algae to sargasso, which may have significant impacts on the overall balance of the trophic structure in these ecosystems. Another potential impact may be the accumulation of metals, imported by sargasso into the system.…”
Section: Other Ecosystemsmentioning
confidence: 99%
“…The drifting mats of sargasso may also serve as a vector for many non-native species [82]. Sargasso also affects the food webs; Cabanillas et al [84] found that sea urchins had changed their diet from reef algae to sargasso, which may have significant impacts on the overall balance of the trophic structure in these ecosystems. Another potential impact may be the accumulation of metals, imported by sargasso into the system.…”
Section: Other Ecosystemsmentioning
confidence: 99%
“…Leachates and particulate organic matter from stranded decaying algal masses depleted the oxygen in near shore waters and reduced visibility of the water column, causing mortality of near-shore seagrasses and fauna (van Tussenbroek et al, 2017;Rodríguez-Martínez et al, 2019). Onshore and near shore masses of sargasso interfered with the seaward journeys of the juvenile turtles (Maurer, De Neef & Stapleton, 2015), affected sea turtle nestings (Maurer, Stapleton & Layman, 2018) and altered the trophic structure of the sea urchin Diadema antillarum in coastal marine systems (Cabanillas-Terán et al, 2019). Massive beachings also enhanced beach erosion (van Tussenbroek et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Leachates and particulate organic matter from stranded decaying algal masses depleted the oxygen in near shore waters and reduced visibility of the water column, causing mortality of near-shore seagrasses and fauna (van Tussenbroek et al, 2017;Rodríguez-Martínez et al, 2019). Onshore and near shore masses of sargasso interfered with the seaward journeys of the juvenile turtles (Maurer, De Neef & Stapleton, 2015), affected sea turtle nestings (Maurer, Stapleton & Layman, 2018) and altered the trophic structure of the sea urchin Diadema antillarum in coastal marine systems (Cabanillas-Terán et al, 2019). Massive beachings also enhanced beach erosion (van Tussenbroek et al, 2017).…”
Section: Manuscript To Be Reviewedmentioning
confidence: 99%